The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1192/bjp.bp.105.015073
|View full text |Cite
|
Sign up to set email alerts
|

Music therapy for in-patients with schizophrenia

Abstract: A randomised trial of music therapy for in-patients with schizophrenia is feasible. The effects and cost-effectiveness of music therapy for acute psychosis should be further explored in an explanatory randomised trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 11 publications
(9 reference statements)
2
89
1
5
Order By: Relevance
“…Of the six studies included in the NICE review, 6 three studies [12][13][14] evaluated the effectiveness of music therapy, two studies 15,16 evaluated the effectiveness of art therapy and one study 17 evaluated the effectiveness of body-orientated psychotherapy. The BPT trial was an exploratory RCT, which tested a manualised form of the intervention in outpatients with persistent negative symptoms of schizophrenia.…”
Section: Body Psychotherapy and Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Of the six studies included in the NICE review, 6 three studies [12][13][14] evaluated the effectiveness of music therapy, two studies 15,16 evaluated the effectiveness of art therapy and one study 17 evaluated the effectiveness of body-orientated psychotherapy. The BPT trial was an exploratory RCT, which tested a manualised form of the intervention in outpatients with persistent negative symptoms of schizophrenia.…”
Section: Body Psychotherapy and Schizophreniamentioning
confidence: 99%
“…A detailed study design description is available in the published protocol. 13 Prior to recruitment, the study was registered through the International Standard Randomised Controlled Trial Number (ISRCTN) system (ISRCTN84216587).…”
Section: Designmentioning
confidence: 99%
“…In 2011, the authors of the first RCT on music and acute psychosis (Talwar et al 2006) published a follow-up editorial in British Journal of Psychiatry where they asked, simply, 'music: it seems to work, but how?' (Talwar et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of music therapy studies with patients who have schizophrenia or schizophrenia-like illnesses concluded that the music therapy intervention, in addition to standard care, could improve patient's global state (Gold, Heldal, Dahle & Wigram, 2005). Research into music therapy with mental health service users has demonstrated improved symptom scores among those randomised to music therapy, especially in general symptoms of schizophrenia (Talwar, et al, 2006).…”
Section: Music Therapy: the Evidencementioning
confidence: 99%